Determination of tropical deforestation rates and related carbon losses from 1990 to 2010. (30th May 2014) - Achard, Frédéric; Beuchle, René; Mayaux, Philippe; Stibig, Hans‐Jürgen; Bodart, Catherine; Brink, Andreas; Carboni, Silvia; Desclée, Baudouin; Donnay, François; Eva, Hugh D.; Lupi, Andrea; Raši, Rastislav; et al.
Abstract: We estimate changes in forest cover (deforestation and forest regrowth) in the tropics for the two last decades (1990–2000 and 2000–2010) based on a sample of 4000 units of 10 ×10 km size. Forest cover is interpreted from satellite imagery at 30 × 30 m resolution. Forest cover changes are then combined with pan‐tropical biomass maps to estimate carbon losses. We show that there was a gross loss of tropical forests of 8.0 million ha yr −1 in the 1990s and 7.6 million ha yr −1 in the 2000s (0.49% annual rate), with no statistically significant difference. Humid forests account for 64% of the total forest cover in 2010 and 54% of the net forest loss during second study decade. Losses of forest cover and Other Wooded Land (OWL) cover result in estimates of carbon losses which are similar for 1990s and 2000s at 887 MtC yr −1 (range: 646–1238) and 880 MtC yr −1 (range: 602–1237) respectively, with humid regions contributing two‐thirds. The estimates of forest area changes have small statistical standard errors due to large sample size. We also reduce uncertainties of previous estimates of carbon losses and removals. Our estimates of forest area change are significantly lower as compared to national survey data. We reconcile recent low estimates of carbon emissions from tropical deforestation for early 2000s and show that carbon loss rates did not change between the two last decades. Carbon losses from deforestation represent circa 10% of Carbon emissions from fossil fuel combustion and cement production during the last decade (2000–2010). Our estimates of annual removals of carbon from forest regrowth at 115 MtC yr −1 (range: 61–168) and 97 MtC yr −1 (53–141) for the 1990s and 2000s respectively are five to fifteen times lower than earlier published estimates.